Introducing Privilege and Oppression in Classrooms - Diwakar G, Dilip; Viswambaran, Visakh (JOURNAL OF INDIAN EDUCATION, 2020)
Education is a powerful tool that can be used to deepen the understanding of systemic privileges and institutionalised oppression present in our society. This paper focuses on a classroom intervention module that seeks to provide an understanding of the concept of privilege and oppression and how it manifests in the Indian context. This module, titled “Privilege and Oppression” is part of a larger intervention addressing intersectional social inequalities arising out of hierarchies of gender, caste, religion and class. The module discusses the concept of privilege and oppression, it forms a base for further discussions on other systemic oppressions. The module uses constructive activities to create an understanding of the concept and uses discussions to build upon the foundation that the students have about privilege and oppression. The reflections of the students are analysed to understand the outcome of the intervention. The analysis of outcomes shows that the module is successful in imparting knowledge about privilege and oppression.